HUBUNGAN KETERGANTUNGAN SMARTPHONE DENGAN NOMOPHOBIA PADA REMAJA DI MADRASAH ALIYAH NEGERI 1 KOTA BOGOR TAHUN 2022 - Gianika Salsa Raharja; agus sumarno (Afiat, 2022)
Adolescence is a period of conflict because usually teenagers want to feel free, but their parents limit their freedom. There are many problems when teenagers are in the adjustment phase, namely juvenile delinquency such as smoking, promiscuity, and smartphone addiction. Smartphone dependence causes users to be unable to control themselves when using smartphones. If teenagers cannot control themselves, this leads to a new anxiety disorder called nomophobia. Apart from nomophobia, there are several impacts of smartphone dependence, such as consumptive behavior, psychological disturbance, and reduced social relations. The purpose of this study was to determine the relationship between smartphone addiction and nomophobia in adolescents at MAN-1 Bogor City. Correlation is a descriptive research method. Samples were taken using the proportional random sampling technique from as many as 151 respondents. Techniques for conducting research using univariate and bivariate analysis with Chi-Square = 5% The results of the study show that there is heavy smartphone dependence (55.6%) and that this has an influence on severe nomophobia (43.7%). The Chi-Square value obtained from the analysis is 85.629a; this value is greater than = 5%, and the hypothesis is rejected. In conclusion, there is a relationship between smartphone dependence and nomophobia in adolescents at MAN-1 Bogor City. There are suggestions that schools are expected to be able to motivate teachers to temporarily turn off the internet when teaching and learning activities are in progress, give group assignments so that there is more interpersonal communication between students, and hold class picket activities so that there is more interaction to minimize the occurrence of smartphone dependence and nomophobia in adolescents